Edge-Oriented Graphene on Carbon Nanofiber for High-Frequency Supercapacitors - Islam, Nazifah; Warzywoda, Juliusz; Fan, Zhaoyang (Nano-Micro Letters, 2017)
High-frequency supercapacitors are being studied with the aim to replace the bulky electrolytic capacitors for current ripple filtering and other functions used in power systems. Here, 3D edge-oriented graphene (EOG) was grown encircling carbon nanofiber (CNF) framework to form a highly conductive electrode with a large surface area. Such EOG/CNF electrodes were tested in aqueous and organic electrolytes for high-frequency supercapacitor development. For the aqueous and the organic cell, the characteristic frequency at − 45° phase angle was found to be as high as 22 and 8.5 kHz, respectively. At 120 Hz, the electrode capacitance density was 0.37 and 0.16 mF cm−2 for the two cells. In particular, the 3 V high-frequency organic cell was successfully tested as filtering capacitor used in AC/DC converter, suggesting the promising potential of this technology for compact power supply design and other applications. Highlights: 1 3D edge-oriented graphene (EOG) was grown encircling carbon nanofiber (CNF) framework to form a highly conductive electrode with a large surface area. 2 EOG/CNF-based supercapacitors in both aqueous and organic electrolytes can response at the kilohertz frequency. 3 3 V high-frequency organic supercapacitor was tested as filtering capacitor used in an AC/DC converter.